HLA footprints on HIV-1 are associated with inter-clade polymorphisms and intra-clade phylogenetic clustering - Matthews, Philippa C; Leslie, Alasdair J; Katzourakis, Aris; Crawford, Hayley; Payne, Rebecca; Prendergast, Andrew; Power, Karen; Kelleher, Anthony D; Klenerman, Paul; Carlson, Jonathan M.; Heckerman, David; Ndung'u, Thumbi; et al. (Journal of Virology, 2009)
The selection of escape mutations has a major impact on immune control of viral infections such as HIV. Viral evasion of CD8+ T-cell responses leaves predictable combinations of escape mutations, termed HLA footprints'. The most clearly defined footprints are those associated with HLA alleles that are linked with successful control of HIV, such as HLA-B*57. We here investigated the extent to which HLA footprint sites in HIV-1 are associated with viral evolution among and within clades. First, we examined the extent to which amino acid differences between HIV-1 clades share identity with sites of HLA-mediated selection pressure, and observed a strong association, in particular with respect to sites of HLA-B selection (p<10-6). Similarly, the sites of amino acid variability within a clade were found to overlap with sites of HLA-selected mutation. Second, we studied the impact of HLA selection on interclade phylogeny. Removing the sites of amino acid variability did not significantly affect clade-specific clustering, reflecting the central role of founder effect in establishing distinct clades. However, HLA footprints may underpin founder strains, and we show that amino acid substitutions between clades alter phylogeny, underlining a potentially substantial role for HLA in driving ongoing viral evolution. Finally, we investigated the impact of HLA selection on within-clade phylogeny, and demonstrate that even a single HLA allele footprint can result in significant phylogenetic clustering of sequences. In conclusion, these data highlight the fact that HLA can be a strong selection force both for intra- and inter-clade HIV evolution at a population level.